The evolutionary game analysis of the decision-making behavior of live streaming stakeholders under the value co-creation - Jia, Shanshan (PloS one, 2023)
Integrity-linked issues have become increasingly serious and attracted considerable attention regarding the sustainability of live streaming; therefore, live streaming anchors and suppliers have become increasingly concerned about their ongoing marketing. Moreover, streaming platforms are also beginning to focus on sustainable development. Determining how live streaming anchor behavior, supplier behavior, and streaming platform strategic decision affect live streaming is essential for achieving the healthy and sustainable development of live streaming ecosystems. However, the game among live streaming anchor behavior, supplier behavior, and streaming platform strategic decisions, which the live streaming ecosystem strongly depends on, has attracted little attention. This study constructed a game model of value co-creation evolution in live streaming ecosystems, with the live streaming anchors, suppliers, and streaming platforms as the main subject. The evolutionary stable strategies of the game were analyzed, and the influence of typical factors on the system was discussed. The results showed that the best evolutionary stability strategy is that live streaming anchors and suppliers choose honesty, and streaming platforms have strict regulation, which is the optimal strategic objective for value co-creation. The appropriate rewards and punishments inherent in a streaming platform can help regulate the behavior of the live streaming anchor and supplier; specifically, great rewards and severe punishments of the streaming platform can be applied to incentivize the honest behavior of the live streaming anchor and supplier. This study provides insights for designing appropriate policies for live streaming platforms to promote sustainable development.